1991
DOI: 10.1302/0301-620x.73b6.1955444
|View full text |Cite
|
Sign up to set email alerts
|

External fixation of intertrochanteric fractures of the femur

Abstract: External fixation was used in the treatment of 154 intertrochanteric fractures of the femur over a period of eight years. Good fixation and early ambulation was achieved in all cases. Blood loss was slight. There were 12 deaths due to medical causes unrelated to the surgical procedure. Deep pin-track infection occurred in six cases and late displacement of the fracture fragments in nine. The average time for union was 16 weeks. The technique is simple, quick and inexpensive, and causes minimal surgical trauma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 4 publications
8
34
2
Order By: Relevance
“…Shortening because of collapse and varisation of the femoral neck is a well-recognized complication of both internal and external fixation in unstable fractures or in the presence of severe osteoporosis [4,5,15]. However, although it also occurred in our study, it was not associated with implant failure or cut out.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Shortening because of collapse and varisation of the femoral neck is a well-recognized complication of both internal and external fixation in unstable fractures or in the presence of severe osteoporosis [4,5,15]. However, although it also occurred in our study, it was not associated with implant failure or cut out.…”
Section: Discussioncontrasting
confidence: 54%
“…Another well-described problem associated with external fixation in the femur is postoperative knee stiffness caused by fixation of the facia lata and vastus lateralis by the distal pins [2,4,13]. This problem was eliminated in our series with the use of the very short pertrochanteric fixator, which allowed the placement of the distal pins quite proximally in the femur.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite these evident advantages, the external fixator has failed to become popular with most surgeons because of the significant reported complications in previous studies, infection being the most common. Cases of deep infection that required pin removal or repositioning have been reported [5]. Vossinakis and Badras [14] reported that pintrack infection developed in 15 of their 50 patients (30%) treated with the Orthofix external fixator using standard pins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on external fixations showed short operating and hospitalization time, high fracture union rate and minimum blood loss 6,7,17,18 .…”
Section: Discussionmentioning
confidence: 97%